2009
DOI: 10.3390/ijerph6082271
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Socioeconomic and Environmental Determinants on Health and Obesity: A West Virginia Case Study

Abstract: A recursive system of ordered self assessed health together with BRFSS data were used to investigate health and obesity in the Appalachian state of West Virginia. Implications of unobserved heterogeneity and endogeneity of lifestyle outcomes on health were investigated. Obesity was found to be an endogenous lifestyle outcome associated with impaired health status. Risk of obesity is found to increase at a decreasing rate with per capita income and age. Intervention measures which stimulate human capital develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 40 publications
(62 reference statements)
5
47
1
Order By: Relevance
“…Obesity could also be a result of market failure [28,60]. Like environmental pollution, it imposes an external cost to society so that public intervention to control obesity is justified.…”
Section: Obesity: a Results Of Market Failure?mentioning
confidence: 99%
See 4 more Smart Citations
“…Obesity could also be a result of market failure [28,60]. Like environmental pollution, it imposes an external cost to society so that public intervention to control obesity is justified.…”
Section: Obesity: a Results Of Market Failure?mentioning
confidence: 99%
“…Like environmental pollution, it imposes an external cost to society so that public intervention to control obesity is justified. In order to reduce the consumption of unhealthy foods, it has been suggested that foods high in calories, fat, or sugar be taxed and that healthy foods such as fruits and vegetables be subsidized [28,61]. A steep tax would probably reduce consumption of taxed foods and could be used to generate funding to subsidize healthful foods; although it was found that fruit and vegetable subsidies were more likely to increase sales, there were mixed opinions on the feasibility and desirability of a steep "junk food" tax [62].…”
Section: Obesity: a Results Of Market Failure?mentioning
confidence: 99%
See 3 more Smart Citations